Parameters of Metabolic Response to Surgical Trauma Induced via Unilateral Total Mastectomy Associated or Not to Ovariohysterectomy in Dogs - Rodigheri, Sabrina Marin; Paiva, Felipe Noleto de [UNESP]; Firmo, Bruna Fernanda; Fuchs, Taise; Mani, Cynthia Bueno; Nardi, Andrigo Barboza de [UNESP] (MDPI, 2023)
Surgical excision of solid tumors is required for local control of neoplasms. However, surgical trauma can stimulate the release of proangiogenic growth factors, suppressing cell-mediated immunity and favoring the development of micrometastases and progression of residual disease. The present study aimed to evaluate the intensity of the metabolic response to trauma induced via unilateral mastectomy in bitches with mammary neoplasia, the consequences of its joint performance with ovariohysterectomy, and their respective effects on the organic response. Two groups of animals were evaluated in seven perioperative moments, namely, unilateral mastectomy (G1) and unilateral mastectomy associated with ovariohysterectomy (G2). Thirty-two female dogs were selected, ten clinically healthy, and twenty-two diagnosed with mammary neoplasia. Surgical trauma reduced serum concentrations of albumin and interleukin-2 but increased blood levels of glucose and interleukin-6 in the postoperative of G1 and G2 patients. Moreover, serum cortisol levels increased after unilateral mastectomy associated with ovariohysterectomy. Our findings allowed us to conclude that unilateral mastectomy induces significant metabolic alterations in female dogs with mammary neoplasms and its joint performance with ovariohysterectomy increases the organic response to trauma.
Keywords: dogs; mammary tumor; oncology; surgical oncology; surgical trauma